2016
DOI: 10.4028/www.scientific.net/kem.711.137
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport Properties and Depth of Chloride Penetration in Ultra High Performance Concrete

Abstract: Properties of water transport and depth of chloride penetration into the Ultra High Performance Concrete (hereafter as UHPC) with mild steel fibres are presented in this paper. The main aim of this experimental part of work is to obtain sufficiently accurate input data for the evaluation of long-term durability of architectural concrete which are connected with water transport and its accompanying effects such as biological degradation or chloride transport. The article also presents the one dimensional chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A study found that the pores have an average diameter less than 5 nm and the volume of the pores is between 1% and 2% of the total volume of the pores in UHPC [73]. It has been found that the water absorption coefficient of UHPC after 90 days is approximately five times lower than that of control concrete [74]. An analysis of one study revealed an average water penetration height and a relative seepage height of 7.2 and 2.2 × 10 −8 mm, respectively, as determined by a single pressure method [75].…”
Section: Water Absorption and Porositymentioning
confidence: 99%
“…A study found that the pores have an average diameter less than 5 nm and the volume of the pores is between 1% and 2% of the total volume of the pores in UHPC [73]. It has been found that the water absorption coefficient of UHPC after 90 days is approximately five times lower than that of control concrete [74]. An analysis of one study revealed an average water penetration height and a relative seepage height of 7.2 and 2.2 × 10 −8 mm, respectively, as determined by a single pressure method [75].…”
Section: Water Absorption and Porositymentioning
confidence: 99%
“…Moreover, UHPC has an outstandingly high compressive strength, making it highly valuable for various construction applications. The minimum compressive strength of UHPC has been reported to be between 160 and 180 MPa [11,12], rendering it highly valu-able for various construction applications, particularly in maintenance and reinforcement engineering [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Since it was invented, UHPC is characterised by a very high compressive strength exceeding 150 MPa and other improved mechanical properties, such as tensile strength, flexural strength, ductility, and impact resistance (de Larrard and Sedran 1994; Yoo and Banthia 2016). In addition, UHPC exhibits favourable behaviour, such as high modulus of elasticity, low creep and shrinkage deformations, and high durability against different exposure conditions, namely, chloride ion penetration resistance and reinforcement corrosion resistance under extreme exposure conditions (Graybeal 2006;Dobias et al 2016;Hassan 2018;Xie et al 2018;Fan et al 2019;Radhi et al 2021). These exceptional properties can generally be achieved using the following approaches.…”
Section: Introductionmentioning
confidence: 99%